Intermittent ischaemic arrest and cardioplegia in coronary artery surgery: coming full circle?. Issue 2 (August 1994) - Taggart, D P; Bhusari, S; Hopper, J; Kemp, M; Magee, P; Wright, J E; Walesby, R
Abstract : OBJECTIVE--To compare the cardioprotective efficacy of cold crystalloid cardioplegia and intermittent ischaemic arrest in patients undergoing elective coronary artery surgery. DESIGN--Prospective randomised trial. SETTING--London teaching hospital. SUBJECTS--20 patients with at least moderately good left ventricular function undergoing elective coronary artery surgery by one experienced surgeon and needing at least two bypass grafts. INTERVENTIONS--Patients were randomised to cold crystalloid cardioplegia or intermittent ischaemic arrest. MAIN OUTCOME MEASURES--The primary determinant of the efficacy of myocardial protection was serial measurement (before and at 1, 6, 24, and 72 hours after the end of cardiopulmonary bypass) of cardiac troponin T (cTnT), a highly sensitive and specific marker of myocardial damage. RESULTS--There was no significant difference in age, ejection fraction, number of grafts, bypass times, or cross clamp times between the two groups. One patient in the cardioplegia group had a perioperative infarct and was excluded from further study. In both groups there was a significant increase in cTnT, with peak concentrations being reached 6 hours after the end of cardiopulmonary bypass and remaining significantly high at 72 hours. At 6 hours the median (75% interquartile range) concentrations of cTnT were similar in both groups (1.8 (1.0-3.6) micrograms/l for cardioplegia v 1.9 (1.0-3.5) micrograms/l for intermittent ischaemic arrest). CONCLUSION--This trial shows that intermittent ischaemic arrest, even without systemic cooling or venting of the left ventricle, provides a similar level of myocardial protection to cardioplegia in patients with moderate left ventricular function and short ischaemic times.